2021
DOI: 10.1109/jlt.2021.3072547
|View full text |Cite
|
Sign up to set email alerts
|

Optimizing Probabilistic Constellation Shaping for Amplifier-Less Coherent Optical Links

Abstract: Coherent optical systems for short-reach links have seen a boost in their popularity with the standardization of 400ZR. These systems need to be cost and power-efficient, while coping with the ever increase in traffic demand. The use of probabilistic constellation shaping (PCS) can help meet these demands, since it reduces the gap to the channel capacity. However, studies concerning PCS typically include optical amplification; therefore, its gain in amplifier-less systems has been somewhat uncertain. In this w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 30 publications
(44 reference statements)
0
8
0
1
Order By: Relevance
“…On a single polarization, we transmit 128 (124) Gbaud 16QAM over 2 (10) km under the 6.7% OH HD-FEC BER threshold of 3.8×10 -3 , which represents a net rate of 480 (465) Gbps. Adopting a higher FEC threshold, we demonstrate the transmission of 128 (124) Gbaud 32QAM over 2 (10) km at a BER below the 2.4×10 -2 threshold of the 20% ⁄ )), as defined in [19]. Considering only the IQM non-linear transfer function, the optimum modulation depth is between 0.5 and 0.6, which addresses the tradeoff between modulation loss and non-linear compression [19].…”
Section: Transmission Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…On a single polarization, we transmit 128 (124) Gbaud 16QAM over 2 (10) km under the 6.7% OH HD-FEC BER threshold of 3.8×10 -3 , which represents a net rate of 480 (465) Gbps. Adopting a higher FEC threshold, we demonstrate the transmission of 128 (124) Gbaud 32QAM over 2 (10) km at a BER below the 2.4×10 -2 threshold of the 20% ⁄ )), as defined in [19]. Considering only the IQM non-linear transfer function, the optimum modulation depth is between 0.5 and 0.6, which addresses the tradeoff between modulation loss and non-linear compression [19].…”
Section: Transmission Resultsmentioning
confidence: 99%
“…Adopting a higher FEC threshold, we demonstrate the transmission of 128 (124) Gbaud 32QAM over 2 (10) km at a BER below the 2.4×10 -2 threshold of the 20% ⁄ )), as defined in [19]. Considering only the IQM non-linear transfer function, the optimum modulation depth is between 0.5 and 0.6, which addresses the tradeoff between modulation loss and non-linear compression [19]. However, the employed RF amplifier 1 dB compression point is 2.5 Vpp, which increases the transmitted signal non-linearity and dedicates operating at a lower modulation depth.…”
Section: Transmission Resultsmentioning
confidence: 99%
“…However, 32QAM performs better than 16QAM for the higher line rates due to the bandwidth limitations primarily from the SiP IQM and the RF amplifiers. Although the transmitter pre-emphasis filters precompensate the signal spectrum up to 64 GHz, the strong equalization after 50 GHz diminishes the AWG output signal swing; resulting in worse RF signal quality, smaller driving swing, higher modulation loss, and lower OSNR [17]. The summary of the achieved transmission rates is tabulated in Table I, considering different FEC thresholds.…”
Section: A Short Iqm (Single Polarization)mentioning
confidence: 99%
“…This impairment has been identified as a peak-power-constraint (PPC), typical to unamplified systems [4]. In [2], we have demonstrated that the application of digital clipping can effectively reduce the PAPR of complex QAM constellations, thereby highly improving the achievable power budget. An important question then arises: is the typical use of QAM formats the most suitable for unamplified transmission?…”
Section: Introductionmentioning
confidence: 98%
“…Targeting the reduction of cost and power consumption, the recent coherent short-reach 400ZR standard already accounts for optical unamplified short-reach systems [1]. However, this option severely affects the power budget, while also introducing a new challenging constraint: due to the absence of a transmitter-side optical amplifier (booster), the system becomes highly sensitive to the peak-to-average power ratio (PAPR) [2,3]. This impairment has been identified as a peak-power-constraint (PPC), typical to unamplified systems [4].…”
Section: Introductionmentioning
confidence: 99%